Human to humanoid motion conversion for dual-arm manipulation tasks. Issue 8 (25th April 2018) - Tomić, Marija; Chevallereau, Christine; Jovanović, Kosta; Potkonjak, Veljko; Rodić, Aleksandar
SUMMARY: A conversion process for the imitation of human dual-arm motion by a humanoid robot is presented. The conversion process consists of an imitation algorithm and an algorithm for generating human-like motion of the humanoid. The desired motions in Cartesian and joint spaces, obtained from the imitation algorithm, are used to generate the human-like motion of the humanoid. The proposed conversion process improves existing techniques and is developed with the aim to enable imitating of human motion with a humanoid robot, to perform a task with and/or without contact between hands and equipment. A comparative analysis shows that our algorithm, which takes into account the situation of marker frames and the position of joint frames, ensures more precise imitation than previously proposed methods. The results of our conversion algorithm are tested on the robot ROMEO through a complex "open/close drawer" task.